Determinants of inappropriate antibiotic prescription in primary care in developed countries with general practitioners as gatekeepers: a systematic review and construction of a framework - Mattijs E Numans; Frederike L Büchner; Martijn Sijbom; Nicholas H Saadah; Mark G J de Boer (BMJ Open)
Objectives This study aimed to identify determinants of inappropriate antibiotic prescription in primary care in developed countries and to construct a framework with the determinants to help understand which actions can best be targeted to counteract development of antimicrobial resistance (AMR).Design A systematic review of peer-reviewed studies reporting determinants of inappropriate antibiotic prescription published through 9 September 2021 in PubMed, Embase, Web of Science and the Cochrane Library was performed.Setting All studies focusing on primary care in developed countries where general practitioners (GPs) act as gatekeepers for referral to medical specialists and hospital care were included.Results Seventeen studies fulfilled the inclusion criteria and were used for the analysis which identified 45 determinants of inappropriate antibiotic prescription. Important determinants for inappropriate antibiotic prescription were comorbidity, primary care not considered to be responsible for development of AMR and GP perception of patient desire for antibiotics. A framework was constructed with the determinants and provides a broad overview of several domains. The framework can be used to identify several reasons for inappropriate antibiotic prescription in a specific primary care setting and from there, choose the most suitable intervention(s) and assist in implementing them for combatting AMR.Conclusions The type of infection, comorbidity and the GPs perception of a patient’s desire for antibiotics are consistently identified as factors driving inappropriate antibiotic prescription in primary care. A framework with determinants of inappropriate antibiotic prescription may be useful after validation for effective implementation of interventions for decreasing these inappropriate prescriptions.PROSPERO registration number CRD42023396225.